Lixiviate production, comparison of the method of Tchobanoglous with experiments in lisimeters - Buchwald de Janon, Federico Von (2019)
Sanitary landfills are the most widely used methods to dispose urban solid waste, its greatest environmental impact is generated by leachate, and there is a generalized criterion that when there are no rains, leachate is not generated. The book Integral Management of solid waste by Tchobanoglous is the greater reference of urban solid waste management and has a procedure for the calculation of leachate production, this was implemented considering a single layer without rainwater influence, which was compared with experimental results of lysimeters with different residue components combinations, finding coincidences in combinations with low content of organic matter but differences in compositions with high contents of organic matter.